2022
DOI: 10.3390/ijms231911775
|View full text |Cite
|
Sign up to set email alerts
|

Methionine 274 Is Not the Determining Factor for Selective Inhibition of Histone Deacetylase 8 (HDAC8) by L-Shaped Inhibitors

Abstract: HDAC8 is an important target in several indication areas including childhood neuroblastoma. Several isozyme selective inhibitors of HDAC8 with L-shaped structures have been developed. A theoretical study has suggested that methionine 274 (M274) would act as a “switch” that controls a transient binding pocket, which is induced upon binding of L-shaped inhibitors. This hypothesis was experimentally examined in this study. The thermostability and functionality of HDAC8 wildtype and mutant variants with exchanged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 32 publications
(67 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, several of the residues that we have identified in this work overlap with previously identified residues; however, in most of the previous investigations, the residues were not deemed critical for selectivity. For example, a recent flexible docking study identified several of the same residues in the KDAC8 binding surface as our MD analysis, including P273, M274, and Y306 as residues that contact a KDAC8 specific inhibitor; however, their work focuses on a specific role for M274 in inhibitor binding, and a follow-up study found that M274 is important for binding but not via the initially proposed mechanism. , Another study identified regions of KDAC8 that displayed high mobility, which may indicate importance for binding, and also identified several of the same residues as this study. Interestingly, they identified two of the three KDAC8 residues that correlated with reduced activity in our study as involved in binding to a KDAC8-specific inhibitor .…”
Section: Discussionmentioning
confidence: 69%
“…Interestingly, several of the residues that we have identified in this work overlap with previously identified residues; however, in most of the previous investigations, the residues were not deemed critical for selectivity. For example, a recent flexible docking study identified several of the same residues in the KDAC8 binding surface as our MD analysis, including P273, M274, and Y306 as residues that contact a KDAC8 specific inhibitor; however, their work focuses on a specific role for M274 in inhibitor binding, and a follow-up study found that M274 is important for binding but not via the initially proposed mechanism. , Another study identified regions of KDAC8 that displayed high mobility, which may indicate importance for binding, and also identified several of the same residues as this study. Interestingly, they identified two of the three KDAC8 residues that correlated with reduced activity in our study as involved in binding to a KDAC8-specific inhibitor .…”
Section: Discussionmentioning
confidence: 69%
“…This last residue, which differs in TRLMS, seems to present a conformation that, like Lys61/Lys67, regulates access to the σ-site. The GR substitution of Leu399 for Met406 could increase the overall flexibility of the pocket by inducing some selectivity in the binding of a ligand [119]. Once the poses of each ligand were chosen, we examined the metastability of the σ-site in both cases.…”
Section: Relevance Of the Pockets Foundmentioning
confidence: 99%
“…The method employed has been described previously [15]. In short, full-length human KDAC8 was produced in E. coli BL21 (DE3) (New England BioLabs ® , Ipswich, MA, USA) with a pET14b vector system (Novagen ® , EMD Millipore, Burlington, MA, USA) containing the KDAC8 gene fused to a N-terminal His6-small ubiquitin-like modifier (SUMO) tag using autoinduction growth media (3.08 g/L KH 2 PO 4 , 3.1 g/L Na 2 HPO 4 * 2 H 2 O, 0.44 g/L MgSO 4 * 7 H 2 O, 0.1% lactose, 0.05% glucose, 0.5% glycerol, and 20 g/L Lennox LB media).…”
Section: Recombinant Production Of Kdac8mentioning
confidence: 99%
“…However, if inhibitors shall be classified according to their binding kinetics, a continuous enzyme activity assay is required, which generates linear progress curves for the enzyme reaction over a long period time, and in the presence of preferably low enzyme concentration [17]. As a starting point for the development of a KDAC8 continuous assay, a two-step endpoint assay was used, which was established in our group [15]. During the first step of this assay the substrate Boc-Lys(TFA)-AMC is deacetylated by the KDAC enzyme.…”
Section: Development and Validation Of The Continuous Kdac8 Activity ...mentioning
confidence: 99%